ON THE DYNAMICS OF THE CIRCUMSTANCES REGARDING THE NUMBER, COMPOSITION, AND LOCALITY OF THE ROMANIANS IN HUNGARY - PETRUȘAN, Gheorghe (Studia Universitatis Babeș-Bolyai Philologia, 2018)
On the dynamics of the circumstances regarding the number, composition, and locality of the Romanians in Hungary. The following pages provide the information necessary to get acquainted with a significant Romanian community left outside the Romanian borders as established in 1918. We look at the dynamics of this population relative to the historical factors which have determined its destiny. The research is based on documents less known to the wide public. The experience of the author, strenghtened by the fact that he is contemporary with the evolution of this community, his entire academic activity, is, in its turm, a bibliographical resource. Rezumat. Dinamica circumstanţelor distribuţiei teritoriale, compoziţiei naţionale şi a numărului românilor din Ungaria. Paginile ce urmează oferă informațiile necesare pentru cunoașterea unei importante comunități românești ce a rămas în afara granițelor României, stabilite la 1918. Privim dinamica acestei populații în funcție de factorii istorici ce i-au determinat destinul. Cercetarea are la bază documente mai puțin cunoscute publicului larg. Experiența autorului, confirmată de faptul că este contemporanul evoluției acestei comunități căreia i-a dedicat întreaga activitate academică, este la rându-i sursă bibliografică. Cuvinte cheie: Românii din Ungaria, majoritate, minoritate, națiune, limbă.